Leveraging Aquaculture and Mariculture for Sustainable Economic Growth in Sri Lanka: Challenges and Opportunities - B. S, Galdolage; E.A, Ekanayake; Al-Daoud, Khaleel Ibrahim; A, Vasudevan; Wenchang, Chen; Hunitie, Mohammad Faleh Ahmmad; Mohammad, Suleiman Ibrahim Shelash (Journal of Ecohumanism, 2024)
Sri Lanka’s strategic location in the Indian Ocean, combined with its rich cultural legacy, has made it a hub for international trade. Recognizing the value of its marine resources, the country has begun to focus on building a blue economy to promote economic advancement, livelihood enhancement, and job creation while safeguarding the ocean ecosystem. The aquaculture and mariculture industries are critical to this endeavor, and understanding their prospects and difficulties is critical to ensuring long-term and equitable development. The qualitative research approach was used, with 20 key-person interviews performed to provide insight into stakeholders’ viewpoints, and the data processed using thematic analysis. Findings highlighted a number of prospects, including the worldwide trend toward aquaculture and mariculture, favorable geographical areas in Sri Lanka for aquaculture and mariculture, a diverse range of species to breed, and shrimp culture. It also identified challenges such as capital, technical, disease, and transportation issues, as well as solutions to those challenges, such as increasing investment in aquaculture and mariculture, improving technology and management practices, encouraging foreign collaboration, developing a regulatory framework, and adding value to production. The sustainable and healthy development of Sri Lanka’s aquaculture and mariculture sectors is critical to economic growth, resource protection, and biodiversity conservation. With the appropriate approach, the blue economy may greatly contribute to the country’s economic prosperity while also protecting its natural resources and cultural heritage.